Economics of contracts in African food systems: Evidence from the malt barley sector in Ethiopia - Delelegne Abera Tefera; Jos Bijman (Agricultural and Food Economics, 2021)
Foreign direct investment (FDI) facilitates modernization of domestic agri-food systems in emerging economies through increased use of vertical coordination. This paper sheds lights on how international brewer investments in African food systems affect smallholder market participation and value chain development. In particular, we analyze the impact of contracts among malt barley producers in Ethiopia. Using cross-sectional survey data, we employ inverse probability-weighted regression adjustment (IPWRA) and propensity score matching (PSM) techniques to analyze the economic impact of contracting. We find that contrary to popular belief, contracting has positive and significant impact on malt barley production, intensification, commercialization, quality improvement, and farm gate prices, ultimately resulting in increased net income and spillover into the productivity of other food crops.
Keywords: 330; Africa; Contract; Ethiopia; Food systems; Impact evaluation; IPWRA; Treatment effect